2019
DOI: 10.1177/1591019919892126
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of recurrent large vessel occlusions treated with repeated thrombectomy

Abstract: Background Repeated mechanical thrombectomy for acute stroke treatment in individual patients has been proven feasible. However, less is known about the etiology of recurrent vessel occlusions after prior thrombectomy. We aimed to understand if the etiology of such recurrent events differs from the first stroke. Methods Retrospectively, we identified all patients at our center who received a repeated mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Similarly, Weber et al 11 found the incidence of recurrent LVO as 1.4%; however, the mean time interval between the first and second MT was 147 days. Ikenberg et al 13 had 1.5% incidence, found 5 patients (21.7%) with recurrent thrombectomy within 24 h and 14 patients (60.9%) within two weeks. Mosimann et al noted that the incidence of early reocclusion after 48 h was 2.3% in patients after successful thrombectomy and Marto et al found that the incidence of early reocclusion after 24 h was 6.6%.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Similarly, Weber et al 11 found the incidence of recurrent LVO as 1.4%; however, the mean time interval between the first and second MT was 147 days. Ikenberg et al 13 had 1.5% incidence, found 5 patients (21.7%) with recurrent thrombectomy within 24 h and 14 patients (60.9%) within two weeks. Mosimann et al noted that the incidence of early reocclusion after 48 h was 2.3% in patients after successful thrombectomy and Marto et al found that the incidence of early reocclusion after 24 h was 6.6%.…”
Section: Discussionmentioning
confidence: 95%
“…To the best of our knowledge, there are five series of 15, 23, 25, 27 and 35 patients (Table 3) and several case reports regarding endovascular treatment of recurrent LVO. [5][6][7][8][9][10][11][12][13][14] In the available series to date, Bouslama et al 5 found that the incidence of recurrent LVO was 2% with the median time interval between the first and last procedure of recurrent LVO being 18 days. Similarly, Weber et al 11 found the incidence of recurrent LVO as 1.4%; however, the mean time interval between the first and second MT was 147 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations